Rapid and sensitive detection of ochratoxin A in rice flour using a fluorescent microsphere immunochromatographic test strip assay. Issue 1 (1st January 2020) - Cheng, Yuan; Liu, Liqiang; Liu, Haiying; Xu, Liguang; Kuang, Hua
ABSTRACT: In this study, a high sensitivity and specificity monoclonal antibody (mAb) was developed based on the hydroxy and carboxy-termini of ochratoxin A (OTA). A fluorescent microsphere immunochromatographic test strip (FM-ICTS) was assembled for the rapid detection the OTA in rice flour. Some relevant parameters were optimized including the best concentration of coating antigen and optimal diluent buffer composition. Under optimal conditions, the strip assay had a visual limit of detection (LOD) of 2 ng/mL and a cut-off value of 16 ng/mL for OTA in rice flour samples. By means of a strip scan reader, we obtained a quantitative measurement for OTA with an LOD of 1.27 ng/mL. No significant difference in the strip test results was seen when compared to an ic-ELISA assay or LC–MS/MS. This also shows, therefore, that the FM-ICTS has potential application for rapid and accurate quantitative detection in the market place.